Molecular Detection of Klebsiella spp. from Buffalo Milk and Farm Environment - Prajapati, Prashant; Kour Chhabra, Daljeet; Gangil, Rakhi; Kumar Bagherwal, Rajendra; Sharda, Rakesh; Sikrodia, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Mastitis caused by Gram-negative bacteria is becoming more common in both well-run and unorganized dairy farms. Coliforms are the major environmental pathogens in the etiology of bovine mammary infections. Among these coliforms, the opportunistic pathogens, Klebsiella spp. may cause the severe mastitis. Klebsiella spp. was isolated from 15 (5.00%) out of total 300 samples. The prevalence of K. pneumoniae in buffaloes and farm environment was 4.66% and 5.33%, respectively. Klebsiella and K. pneumoniae were recovered from all type of samples, viz., mastitic milk, faeces, bedding material and floor, drinking water and soil sample. The prevalence of virulence gene (fimH) in Klebsiella spp. isolated from buffaloes and farm environment was 53.33%.